(untitled) - Leung, Wallace Woon-Fong (Oxford, 2007)
This book is the first devoted to centrifugal separation in biotechnology. It is of value to professionals in the chemical, bioprocess, and biotech sectors, and all those concerned with bioseparation, bioprocessing, unit-operations and process engineering. Key topics covered include a full introduction to centrifugation, sedimentation and separation; detailed coverage of centrifuge types, including batch and semi-batch centrifuges, disk-stack and tubular decanter centrifuges; methods for increasing solids concentration; laboratory and pilot testing of centrifuges; selection and sizing centrifuges; scale-up of equipment, performance prediction and analysis of test results using numerical simulation. A comprehensive guide to centrifuges, their optimal development and operation in the biotechnology industry Applications for the separation of proteins, DNA, mitochondria, ribosomes, lysosomes and other cellular elements Provides detailed process information and data to assist in the development of particular processes from existing systems Explores the commercial applications of centrifuges in biotechnology Guidance on troubleshooting and optimizing centrifuges
Keywords: Centrifugation,Biotechnology,Công nghệ Sinh học; Methodology,Phương pháp luận